Joint power and bandwidth allocation in IEEE802.22 based cognitive LTE network - Asheralieva, Alia; Mahata, Kaushik (Computer networks (Amsterdam, Netherlands : 1999), 2014)
We investigate the problem of energy-efficient dynamic spectrum access (DSA) in a cognitive Third Generation Partnership Project (3GPP) long-term evolution (LTE) network based on IEEE802.22 architecture. In this architecture, the network resources are allocated to the end-users and the evolved NodeBs (eNBs) by the spectrum manager (SM) using some optimal resource allocation strategy. In particular, we propose to assign the bandwidth and transmission power to the uplink and downlink of LTE system so that the total transmission power is minimized subject to capacity constraints, queue stability constraints, and some integer restrictions on the bandwidth. To find the buffer occupancy in the system, we use modified Shannon expression which depends on signal-to-noise ratio (SNR) and modulation and coding scheme (MCS). Unlike previous works, the proposed resource allocation algorithm is derived based on realistic assumptions, such as discrete spectrum resources, relation between transmission rate, MCS and the channel quality. Performance of the algorithm is evaluated using simulations in OPNET environment. The algorithm shows consistent performance improvement when compared with other relevant resource allocation techniques.